2021
DOI: 10.1186/s12864-021-07817-6
|View full text |Cite|
|
Sign up to set email alerts
|

Genome wide effects of oleic acid on cultured bovine granulosa cells: evidence for the activation of pathways favoring folliculo-luteal transition

Abstract: Background Metabolic stress, as negative energy balance on one hand or obesity on the other hand can lead to increased levels of free fatty acids in the plasma and follicular fluid of animals and humans. In an earlier study, we showed that increased oleic acid (OA) concentrations affected the function of cultured bovine granulosa cells (GCs). Here, we focus on genome wide effects of increased OA concentrations. Results Our data showed that 413 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…Moreover, studies in mice [ 151 , 153 , 154 , 155 , 156 , 157 ], humans [ 158 ], bovines [ 150 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ], pigs [ 85 , 169 , 170 , 171 ], and sheep [ 172 ] demonstrated that the lipid profile alteration resulted in lipotoxicity in the follicular cells and oocyte. Follicular cell biological functions were affected in their viability, proliferation, ROS production, lipid storage, and ER stress response which ultimately resulted in apoptosis.…”
Section: High-fat Diet Impact On Oocyte Developmental Competencementioning
confidence: 99%
“…Moreover, studies in mice [ 151 , 153 , 154 , 155 , 156 , 157 ], humans [ 158 ], bovines [ 150 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ], pigs [ 85 , 169 , 170 , 171 ], and sheep [ 172 ] demonstrated that the lipid profile alteration resulted in lipotoxicity in the follicular cells and oocyte. Follicular cell biological functions were affected in their viability, proliferation, ROS production, lipid storage, and ER stress response which ultimately resulted in apoptosis.…”
Section: High-fat Diet Impact On Oocyte Developmental Competencementioning
confidence: 99%
“…1 E ). Stearate is a direct substrate for oleate biosynthesis by the enzyme stearoyl CoA desaturase, which is abundantly expressed in GCs ( 34 , 35 ). Therefore, the decrease of estradiol at higher stearate concentrations than its lower concentrations might be because of the increased biosynthesis of oleic acid from the exogenous stearate.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported a genome-wide transcriptome analysis of GCs treated with OA (GEO reference: GSE152307) ( 35 ). In the present study, we have reanalyzed the datasets and identified significantly regulated genes using false discovery rate (FDR) (q) <0.05 without considering the fold change cutoff value, which was previously used as a stringent selection criterion for identifying differentially regulated genes.…”
Section: Resultsmentioning
confidence: 99%
“…Prediction of their downregulation in this study implies that the EMT from GCs to luteal cells was possibly inhibited in vitro in the presence of COCs and NEFAs. A recent study suggested that increased concentrations of oleic acid (OA) may promote the EMT process in bovine GCs [26]. Oleic acid was Fig.…”
Section: Inhibited Luteinization Of Cocultured Gcs Under Elevated Nef...mentioning
confidence: 99%